Nonalcoholic Fatty Liver Disease, Cardiovascular Risk, and Carotid Inflammation - Al-Rasadi, Khalid (2015)
Nonalcoholic fatty liver disease (NAFLD) is defined by excessive triglycerides (TGs) accumulation in the liver (>5% of hepatocytes histologically) in the absence of alcohol excess. The NAFLD ranges from simple steatosis to steatohepatitis and cirrhosis. The NAFLD and nonalcoholic steatohepatitis (NASH) are now the number one cause of liver disease in Western countries. The prevalence of NAFLD is increasing but is underreported, and the epidemiology and demographic characteristics vary worldwide.2 The prevalence is increasing because of the rising occurrence of obesity and type 2 diabetes (T2DM); in fact, NAFLD is considered as the hepatic manifestation of metabolic syndrome (MetS).